Description of Behavior of Community's Healthy Lifestyle in Buibau Village Baucau District Timor Leste - Ornai, Joao Cristovao Neto Mok; Da Costa, Horacio Sarmento; Dos Santos, Andre Soares (Jurnal Sehat Indonesia (JUSINDO), 2025)
The importance of maintaining a healthy lifestyle in a community is critical, particularly when data indicates a high incidence of lifestyle-related diseases. For instance, in Buibau Village, Baucau District, Timor Leste, 98 individuals suffer from hypertension, diarrhea, and other preventable conditions, emphasizing the need for a focus on healthy lifestyle behaviors. This study aims to assess the community’s healthy lifestyle behaviors in Loidua Hamlet, Buibau Village, Baucau District. The research uses a descriptive approach with a survey design, conducted from April 1 to April 3, 2018. The population consisted of 216 residents aged ≥14 years, with 68 respondents selected through accidental sampling. Data collection was carried out using structured questionnaires, and data analysis involved descriptive statistics to categorize the health behaviors observed. The findings reveal that 58.8% of respondents exhibit good healthy lifestyle behaviors, particularly in maintaining a balanced diet, engaging in regular physical activity, and practicing hand hygiene. However, issues such as a lack of awareness regarding stress management and substance abuse were noted. These behaviors reflect the community’s need for continuous health education. In conclusion, although there is a positive trend in healthy lifestyle behaviors, further educational interventions are required to address areas such as stress management and substance avoidance. Health institutions are encouraged to use these findings as a foundation for improving health education in the community and promoting sustainable health practices.